2011
DOI: 10.1007/s10522-011-9322-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of estrogen deficiency in skin ageing and wound healing

Abstract: The links between hormonal signalling and lifespan have been well documented in a range of model organisms. For example, in C. elegans or D. melanogaster, lifespan can be modulated by ablating germline cells, or manipulating reproductive history or pregnenolone signalling. In mammalian systems, however, hormonal contribution to longevity is less well understood. With increasing age human steroid hormone profiles change substantially, particularly following menopause in women. This article reviews recent links … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 258 publications
(163 reference statements)
3
111
0
2
Order By: Relevance
“…Considering that our samples were exclusively derived from female volunteers, it seems reasonable to link the latter window to menopause, which is also known to distinctly accelerate skin aging (Thornton, 2013). The high temporal and spatial specificity of these methylation changes suggests that defined signaling pathways, such as estrogen signaling (Emmerson & Hardman, 2012), may be involved in their establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that our samples were exclusively derived from female volunteers, it seems reasonable to link the latter window to menopause, which is also known to distinctly accelerate skin aging (Thornton, 2013). The high temporal and spatial specificity of these methylation changes suggests that defined signaling pathways, such as estrogen signaling (Emmerson & Hardman, 2012), may be involved in their establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of aromatase (Arimidex, 100 nM) and STS (STX64, 100 nM) were included alone or in combination with relevant steroids. Migration was measured at 4,8,12,24, and 48 h in triplicate dishes for each donor. Conditioned medium, collected from dermal fibroblast cultures 24 h after scratching as previously described (37), was also assessed for its effect on the migration of epidermal keratinocytes.…”
Section: Scratch Wound and Cell Migration Assaymentioning
confidence: 99%
“…DHEA-S, DHEA, and 17b-estradiol but not testosterone stimulates the migration of wounded human epidermal keratinocytes and dermal fibroblasts in vitro A scratch assay as previously described (28, 30) measured epidermal keratinocyte (n = 3) and dermal fibroblast (n = 5) migration in response to 10 mM DHEA-S, 10 mM DHEA, 1 nM 17b-estradiol or 50 nM testosterone at 5 fixed time points (4,8,12,24, and 48 h). Previous dose-response assays using this technique have shown that a range of concentrations of 17b-estradiol (10 27 -10 29 M) and DHEA (10 25 -10 28 M) all stimulated cell migration to a similar level (37,39).…”
Section: Cultured Human Dermal Fibroblasts and Epidermal Keratinocytementioning
confidence: 99%
See 2 more Smart Citations